Corrosion characteristics of aluminium alloys in calophyllum inophyllum biodiesel / Raja Nurul Hani Raja Azhar - Raja Nurul Hani, Raja Azhar (2017)
Biodiesel is one of the attractive alternatives to cater the limited petroleum diesel sources in future due to its environmental benefit and domestic producibility. However, one of the drawbacks of biodiesel is its corrosive property. In this work, corrosion characteristics of commercial aluminium alloy 3003, 5052 and 6061 in various Calophyllum inophyllum biodiesel blends is studied and analyzed. Immersion test of aluminium alloy 3003, 5052 and 6061 is carried out in Calophyllum inophyllum biodiesel blends B0, B5, B10 and B15 for 1200 hours at room temperature. The corrosion rate of aluminium alloy 3003, 5052 and 6061 in Calophyllum inophyllum biodiesel blends B0, B5, B10 and B15 is calculated from the weight loss obtained after the immersion test. The surface morphology after immersion test is observed by using scanning electron microscopy (SEM). Result shows that aluminium alloy 3003 is the most susceptible to corrosion in Calophyllum inophyllum biodiesel blends compared to aluminium alloy 5052 and 6061. Keywords: corrosion, aluminium, biodiesel.